مقارنة بين الطرق الرقمية في تمثيل السطوح الأثرية وإنشاء المقاطع الشاقولية (قلعة الخوابي- طرطوس) - عبد الرزاق عجاج; إياد عباس (Tishreen University, 2017)
يعتبر التمثيل الثلاثي البعد للمنشآت الهندسية مرحلة مهمة في سياق التعبير الهندسي عن المنشآت والتصميم والإجراءات الهندسية اللاحقة التي ستنفذ. من هذا المنطلق يهدف بحثنا إلى المقارنة بين طرق التمثيل الرقمي الثلاثي البعد للمنشآت المدنية ذات الاستخدامات الخاصة ومنها المنشآت الأثرية من أجل الأعمال اللاحقة (توثيق، ترميم) وسهولة الحصول على المقاطع العرضية. أجريت المقارنة الفنية والاقتصادية بين طرق ثلاث: 1- الطريقة التقليدية باستخدام البرامج الحديثة civil 3d وبرامج التصوير الرقمي باستخدام أجهزة الهاتف المحمول وبرامجه الموافقة. 2- باستخدام برمجيات نظم المعلومات الجغرافية GIS وامكانياته المختلفة. 3- إمكانية استخدام الماسح الضوئي الليزري Laser scanner. واعتمد في المفاضلة كمعيار حاسم على تحقيق الشروط الفنية والمردود الاقتصادي الأعظمي. The 3Dimension representation of facilities engineering an important stage in the context of the expression of the engineering facilities and design engineering and subsequent action to be carried out. From this point of our research is designed to compare the methods of digital representation triple dimension to civilian facilities with special uses, including the archaeological monument for subsequent Business (documentation, restoration) and ease of access to cross-sections. Technical and economic comparison was conducted between three ways : 1. The traditional way using modern civil 3d programs and programs of digital photography using mobile phone hardware and software approval. 2. Using the different potential of Geographic Information Systems, GIS software. 3. The possibility of using a Laser scanner And adopted as a standard in the comparison the method that gives maximum of economy to achieve the technical conditions.